THE EFFECT OF PROBIOTIC ADDITION IN MOIST FEED ON THE GROWTH OF SAND LOBSTER (Panulirus homarus) - Lutfah Yunata Pratiwi; Muhammad Junaidi; Nuri Muahiddah (Jurnal Perikanan Unram, 2024)
Lobsters are a potential fishery commodity with significant economic value. An alternative feed option that can be used is artificial feed, such as moist feed. One commonly known probiotic in the market is EM4, which can be used as a feed additive and can increase protein content to support growth processes. This study aims to determine the optimum probiotic dosage in moist feed to enhance the growth of sand lobsters (Panulirus homarus). The findings of this research are intended to provide insights and benefits for further research or practical applications. This study used an experimental method with a completely randomized design (CRD). It involved five treatments with three replications, resulting in 15 experimental units. The treatments included P0 (control), P1 (moist feed without probiotics), P2 (moist feed + 0.1% probiotic), P3 (moist feed + 0.2% probiotic), and P4 (moist feed + 0.3% probiotic). The results showed that after maintaining Panulirus homarus for 60 days in Teluk Ekas, the addition of different probiotic levels in moist feed produced the following average outcomes: absolute length growth ranged from 3.19 to 4.76 cm, absolute weight growth ranged from 42.90 to 62.30 g, specific growth rate ranged from 1.71 to 2.14 g, feed conversion ratio (FCR) ranged from 5.05 to 6.69, feed efficiency ranged from 69.12% to 87.26%, and survival rate ranged from 70% to 90%. Based on these findings, it can be concluded that the best treatment for absolute length growth, absolute weight growth, specific growth rate, feed efficiency, and FCR was P4 (moist feed + 0.3% probiotic), while the best survival rate was achieved in P2 (moist feed + 0.1% probiotic).